Optimasi Hidrolika Dengan Metode BHHP Pada Trayek 8-1/2 Inch Sumur KB Lapangan X4 - Aulia Huda Pinandita; Aly Rasyid; Muhammad Al Hafiz Mattauch (Jurnal Bhara Petro Energi, 2025)
This research focuses on optimizing drilling hydraulics in Well “KB”, Field “X4”, to increase the efficiency of drilling operations and lifting cuttings through a mud circulation system. Drilling mud plays an important role in lifting rock chips, maintaining hydrostatic pressure, and preventing formations from rising to the surface. The optimization method used is Bit Hydraulic Horse Power (BHHP) which measures pump performance and the strength of the mud flow through the bit to ensure maximum lifting power. The parameters analyzed include mud flow rate, viscosity, pump pressure, and nozzle size. The research results show that optimal hydraulic parameter settings can increase the rate of penetration (ROP) and drilling efficiency. Controlling factors such as mud density, flow rate and mud gel strength is key in maintaining drill hole stability and reducing drilling time. This research contributes to the development of drilling technology, especially in drilling mud management, which supports the efficiency and safety of drilling operations in oil fields.